(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2026)
Background: The Brazilian banking sector combines private and state-owned publicly traded banks, articulating market practices and state guidelines, which creates governance challenges. This structural diversity requires understanding how the type of control influences incentives and practices such as board independence, compliance, transparency, and minority representation. Purpose: This study aimed to identify the differences in corporate governance practices between Banco do Brasil S.A. and the main private banks in the country Method: The research adopts a multiple case study to analyze governance practices in four Brazilian banks (state-owned and private). Data collection was conducted through documentary analysis of reports and official codes from the last five years, extracted from reliable sources such as B3, CVM (Securities and Exchange Commission), and the Central Bank. Results: In general, the banks meet the minimum requirements, but differ in how they internalize regulatory pressures, market demands, and social expectations. All converge on essential practices, reflecting strong regulation and the importance of trust. The differences arise in the depth of these practices: Banco do Brasil stands out for Novo Mercado and IGG (Integrated Governance and Management Index), Itaú for its reputation, Bradesco for its professionalized management, and Santander for its global compliance standards. Conclusions: The study demonstrates that corporate governance in the Brazilian banking sector results from the interaction between ownership, regulation, and institutional objectives, rather than from a single model.